Dynamic effects of fixed orthodontic treatment on oral health and oral microbiota: a prospective study - Mei Zhao; Chaoran Yu; Chengjun Su; Haiyan Wang; Xiaoyu Wang; Michael D. Weir; Hockin H. K. Xu; Min Liu; Yuxing Bai; Ning Zhang (BMC Oral Health)
Abstract Objective This prospective clinical study examined the effects of fixed orthodontic appliances on oral hygiene and assessed changes in the oral microflora structure of orthodontic patients using high-throughput sequencing technology. Methods A total of 45 patients undergoing initial fixed orthodontic treatment were recruited from three hospitals in Beijing, China. Clinical parameters and oral hygiene habits questionnaire were recorded at pre-treatment (T0) and at a 6-month follow-up (T1). Saliva samples were collected for DNA extraction, PCR amplification, 16S rRNA gene sequencing, and bioinformatics analysis. Microbial diversity and structural changes in abundance were evaluated. Results After six months of orthodontic treatment, patients’ daily brushing frequency increased (P ≤ 0.01), while the plaque index and the debris index decreased. A total of 3,344,549 valid tags were obtained from 90 saliva samples. After the six-month follow-up, the microbial diversity in patients’ saliva samples increased significantly. High-throughput sequencing identified 3,662 amplicon sequence variants (ASVs), with the dominant phyla being Proteobacteria, Bacteroidota, Firmicutes, Actinobacteriota, Fusobacteriota, Patescibacteria, Campylobacterota and Spirochaetota. At the phylum level, the abundance of Firmicutes_C and Spirochaetota at T1 significantly increased compared to T0. Conclusion During fixed orthodontic treatment, although patients’ oral hygiene habits improved, significant changes in the oral microbiota structure were still observed, with an increase in anaerobic and pathogenic bacteria that may potentially impact oral health.